A significant antibiofilm and antimicrobial activity of chitosan-polyacrylic acid nanoparticles against pathogenic bacteria - O'la AL-Fawares; Areen Alshweiat; Rozan O. Al-Khresieh; Kawthar Z. Alzarieni; Ayat Hussein B. Rashaid (Elsevier, 2024)
Chitosan is known to exert antimicrobial activity without the need for any chemical modification; however, new derivatives of chitosan can be created to target multi-drug resistant bacteria. In this study, chitosan (CS) was cross-linked with sodium tripolyphosphate to form nanoparticles, which were then coated with polyacrylic acid (PAA). The SEM images revealed that the CS-PAA nanoparticles had spherical shapes with smooth surfaces and the size of the dried nanoparticles was approximately 222 nm. Biofilm formation was significantly inhibited by 0.5 mg/mL of CS-PAA. In-situ optical microscopy showed that CS-PAA nanoparticles inhibited the bacterial biofilm formation in Campylobacter jejuni, Pseudomonas aeruginosa, and Escherichia coli after a single treatment with 40 μg. Additionally, 20 µg of CS-PAA nanoparticles demonstrated antibacterial activity against the growth of C. jejuni, P. aeruginosa, and E. coli with notable inhibitory zones of 9, 12, and 13 mm, respectively (P < 0.01). The development of a novel and ecofriendly method for the preparation of chitosan nanoparticles through an interaction of chitosan with PAA shows promise tool to combat bacterial infections and validates effective antibacterial and antibiofilm properties against antibiotic resistant pathogens.